The Effect of the Varied Style on Learning Basic Stances and Footwork in Foil Fencing for Students - Namus, Shahad; Kazim, Taghrid; Rashid, Murtadaa (Indonesian Journal Publisher, 2026)
This study examines the influence of different teaching methods on university students at beginner and intermediate levels in learning the fundamentals of foil fencing, particularly stance and footwork. It highlights that traditional instructional approaches may not adequately address individual differences in motor learning, which can limit student engagement and skill development despite their interest in the sport. Objective, The study aims to compare the effectiveness of various teaching methods (such as adaptive learning strategies, task variability, and interactive instruction) with traditional instructor-centered methods in improving students’ technical performance and motor skill acquisition in fencing. Method, A sample of 40 University of Diyala students were split into experimental and control groups using an experimental design. Five fundamental fencing abilities were evaluated in pre- and post-tests for both groups: Basic Stance, On-Guard stance, Forward movement (Advance), Retreat, and Lunge technique. Paired and independent t-tests were used to assess the data. Results, According to the findings, the experimental group outperformed the control group in terms of coordination, movement efficiency, and technical execution. Using a variety of instructional approaches greatly improved performance retention, engagement, and skill gain. Conclusion, The research comes to the conclusion that when it comes to improving fencing skills, student-centered and adaptable teaching strategies work better than conventional ones. In order to improve coaching efficacy, it suggests using contemporary teaching techniques and technology-assisted learning, as well as investigating long-term skill retention and applying such approaches across different sports disciplines.